INTERPRETATION OF THE POSITION OF THE CORRUPTION ERADICATION COMMISSION AS AN EXECUTIVE AGENCY - Jauhar Nashrullah (Universitas Syiah Kuala, 2023)
The shift in the institutional position of the KPK (Corruption Eradication Commission) as an executive agency has brought various discourses and pros and cons in the community. This research aims to contribute to the field of thought by interpreting the institutional position of the KPK in Indonesia from the perspective of the six modalities of constitutional argument theory. This research uses normative juridical research methods with statutory, conceptual, and case approaches. Through in-depth analysis of all legal materials (primary and secondary), the research results provide an understanding that through textual, historical, structural, doctrinal, ethical, and prudential interpretations, it is concluded that the actual institutional change of the KPK to the executive is not unconstitutional. However, designing the KPK institution should not only be based on textual provisions and originality of authority, it is necessary to explore constitutional morality and ethics. Moreover, if analyzed in historical, doctrinal, moral, prudential, and ethical aspects, the KPK is more appropriately designed as an independent state commission. KPK bears tremendous responsibility and hopes to eradicate corruption, which has hindered achieving the nation's goals. Therefore, the independence of the KPK needs to be safeguarded from the intervention of other powers.